Association Of the BMP4 Genes Polymorphism with Physiological Traits - Abdullah, Boraq Jaafar; alkhanjer, Sajad; Abid, Ali R. (Journal of Neonatal Surgery, 2025)
Bone morphogenetic proteins (BMPs) are members of the transforming growth factor-β family of proteins that have been implicated in the paracrine regulation of granulosa cell (GC) function , The growth and development of follicles within the ovary are highly dependent on autocrine and paracrine signaling involving growth factors from granulosa cells, theca cells, stromal interstitial cells, and the oocytes, The growth factor bone morphogenetic protein-4 (BMP-4) and its receptor (BMPR-IB) have been detected in ovaries, The objective of the current study was designed to Association of the BMP4 genes polymorphism with physiological traits in Iraqi cattle. So far, more than 30 members have been identified in the BMP family of which BMP4 is the most important one. BMP4 can inhibit progesterone production by granulosa cells and decrease basal granulosa cells progesterone secretion and totally abolish FSH-stimulating action both in cattle and sheep. BMP-4 promotes primordial follicle development and the primordial-to-primary follicle transition, BMP-4 plays an important role in promoting the survival and development of primordial follicles in the neonatal ovary. The expression and function of bone morphogenetic protein 4 (BMP4) gene in bovine cumulus cells (CCs) was investigated to reveal the mechanisms by which it regulated cell apoptosis and proliferation. BMPs are intra-ovarian factors expressed in mammalian ovaries by oocytes, granulosa and theca cells.